2018
DOI: 10.1016/j.envpol.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The multilevel antibiotic-induced perturbations to biological systems: Early-life exposure induces long-lasting damages to muscle structure and mitochondrial metabolism in flies

Abstract: Antibiotics have been increasingly used over the past decades for human medicine, food-animal agriculture, aquaculture, and plant production. A significant part of the active molecules of antibiotics can be released into the environment, in turn affecting ecosystem functioning and biogeochemical processes. At lower organizational scales, these substances affect bacterial symbionts of insects, with negative consequences on growth and development of juveniles, and population dynamics. Yet, the multiple alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Such studies improve our understanding of the ecological effects of pollution on wildlife (Saaristo et al, 2018). So far, a range of works have examined the effects of pesticides (Dewer et al, 2016;Serra et al, 2020;Engell Dahl et al, 2021), heavy metals (Berni et al, 2019;Cosio and Renault, 2020), pharmaceuticals (Prud'homme et al, 2018;Renault et al, 2018) or polymers (de Souza Machado et al, 2018;Kögel et al, 2020) on the biology and physiology of plants and insects. In ACCEPTED MANUSCRIPT -CLEAN COPY 4 addition to describing the conspicuous impacts on growth and development, these investigations have revealed the latent effects pollutants can have on the ecology and biology of wildlife.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies improve our understanding of the ecological effects of pollution on wildlife (Saaristo et al, 2018). So far, a range of works have examined the effects of pesticides (Dewer et al, 2016;Serra et al, 2020;Engell Dahl et al, 2021), heavy metals (Berni et al, 2019;Cosio and Renault, 2020), pharmaceuticals (Prud'homme et al, 2018;Renault et al, 2018) or polymers (de Souza Machado et al, 2018;Kögel et al, 2020) on the biology and physiology of plants and insects. In ACCEPTED MANUSCRIPT -CLEAN COPY 4 addition to describing the conspicuous impacts on growth and development, these investigations have revealed the latent effects pollutants can have on the ecology and biology of wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…In ACCEPTED MANUSCRIPT -CLEAN COPY 4 addition to describing the conspicuous impacts on growth and development, these investigations have revealed the latent effects pollutants can have on the ecology and biology of wildlife. The insidious nature of xenobiotics toxicity includes, for instance, deleterious effects of antibiotics on the muscle structure of flies (Renault et al, 2018), impacts of ibuprofen on the development of mosquitoes (Prud'homme et al, 2018), or cryptic effects of low doses of pesticides on plant metabolism (Serra et al, 2013) and animal behavior (Desneux et al, 2007;Hanlon and Relyea, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic treatment may inhibit formation of a peritrophic matrix around the blood bolus after blood-feeding [81], thereby enhancing the possibility of virus particles to interact with the midgut epithelial cells. Furthermore, it was shown that antibiotics can induce long-lasting damaging effects on muscle structure and mitochondrial metabolism in blow flies [84]. Similar effects on midgut cells may result in a "leaky gut," which is a well-described physiological change in insect vector midgut cells that results in increased virus infection [66,85,86].…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…These pollutants, which can persist over the long term, can greatly threaten biodiversity (Santos et al 2010;Richmond et al 2016). For instance, in a recent study, Renault et al (2018) experimentally evidenced the deleterious effects of antibiotics on the development and survival of the blow fly Chrysomya albiceps. In mosquitoes, chronic exposure of the parental generation to the antiinflammatory ibuprofen had consistent effects on the progeny by accelerating their development and increasing their capacity to handle starvation periods (Prud'homme et al 2018).…”
Section: Introductionmentioning
confidence: 99%